Mildronate decreases carnitine availability and up-regulates glucose uptake and related gene expression in the mouse heart - Liepinsh, Edgars; Vilskersts, Reinis; Skapare, Elina; Svalbe, Baiba; Kuka, Janis; Cirule, Helena; Pugovics, Osvalds; Kalvinsh, Ivars; Dambrova, Maija (Life sciences (1973), 2008)
l-carnitine has been shown to play a central role in both fat and carbohydrate metabolisms. This study investigated whether acute and long-term treatments with an l-carnitine biosynthesis inhibitor, mildronate (3-(2,2,2-trimethylhydrazinium) propionate), modulate glucose uptake. The effects of acute and long-term administration of mildronate at a dose of 200 mg/kg (i.p. daily for 20 days) were tested in mouse blood plasma and heart. Acute administration of mildronate in vivo, or in vitro administration with perfusion buffer in isolated heart experiments, did not induce any effects on glucose blood concentration and uptake in the heart. Mildronate long-term treatment significantly decreased carnitine concentration in plasma and heart tissues, as well as increased the rate of insulin-stimulated glucose uptake by 35% and the expression of glucose transporter 4, hexokinase II, and insulin receptor proteins in mouse hearts. In addition, expression of both carnitine palmitoyltransferases IA and IB were significantly increased. Mildronate long-term treatment statistically significantly decreased fed state blood glucose from 6 ± 0.2 to 5 ± 0.1 mM, but did not affect plasma insulin and C-peptide levels. Our experiments demonstrate for the first time that long-term mildronate treatment decreases carnitine content in the mouse heart and leads to increased glucose uptake and glucose metabolism-related gene expression.